EDUKASI TENTANG COVID-19 DAN ADAPTASI ERA NEW-NORMAL LIFE DI DESA KUTUWETAN KECAMATAN JETIS KABUPATEN PONOROGO - Wiwiek Retti Andriani; Agus Wiwit Suwanto (Jurnal IDAMAN (Induk Pemberdayaan Masyarakat Pedesaan), 2021)
The government's policy of removing large-scale social restrictions (PSBB) and the existence of a new-normal life policy have generated mixed perceptions and responses in the people of Kutuwetan Village, Jetis District, Ponorogo Regency. Many residents do not comply with the health protocol regarding wearing masks and washing hands on the grounds that there are new-normal recommendations (normal life). This is related to public knowledge of Covid-19 and how to live healthy behavior in the new-normal life. Therefore, community empowerment is very necessary to increase knowledge so that there is a change in people's behavior to reduce the transmission of Covid-19. The purpose of this activity is to change people's behavior by increasing knowledge and empowering the community. The activities carried out are in the form of structured education in several sessions for sub-district and village officials, representatives of community leaders, representatives of TP-PKK mothers, and representatives of Karang Taruna in Kutuwetan Village. The results of the implementation of the activities were evaluated using a questionnaire that was measured pre-post, with the average result of the pre-test score being 95% in the category of sufficient knowledge, while the post-test results the test obtained 70% good knowledge category, then there is an increase in knowledge about Covid-19 and how to prevent it as well as changes in people's behavior in clean and healthy living which is seen from washing hands, wearing masks, keeping a distance. The output of the activity is in the form of journal publication. The follow-up evaluation was carried out with the Kutuwetan Village Satgas (task-force) Covid-19.